Kontribusi Lingkungan Sosial terhadap Keputusan Perceraian di Jawa Barat: Analisis Regresi Logistik pada Data SUSENAS 2022 - Julpani, Asti Engla; Ridwan, Endrizal (SAFE-Network, 2025)
The high divorce rate in West Java Province underscores the need for an in-depth examination of environmental factors influencing individuals’ decisions to divorce. This study aims to analyze the impact of social environments with high divorce rates on individual divorce decisions, while accounting for control variables such as working hours, education level, and age at marriage. Using data from the 2022 National Socio-Economic Survey and a binary logistic regression approach, the study finds that individuals living in areas with high divorce rates are 1.645 times more likely to get divorced p < 0.001. Early marriage also shows a significant effect OR = 1.098; p < 0.05. In contrast, working hours and education are not statistically significant. These findings highlight the urgency of community-based interventions and social policies that are sensitive to local norms.